PERSEPSI DAN SIKAP PEKERJA TERHADAP PETERNAKAN AYAM PETELUR MILIK PAK DASMAN DI DESA PAL VIII KECAMATAN BERMANI ULU RAYA KABUPATEN REJANG LEBONG - Septian Derianti; Basuki Sigit Priyono; Bambang Sumantri (Wahana Peternakan, 2023)
This study aims to (1)Analyzing employee perceptions of Pak Dasman's laying hens farm, (2) Analyzing employee attitudes towards Pak Dasman's laying hens farm(3)Analyze what factors are related to employee perceptions of Pak Dasman's laying hens farm, (4) Analyzing the relationship between employee perceptions and attitudes towards Mr. Dasman's laying hens farm. Determination of the location in this research is done purposively (deliberately). This research was conducted in Pal VIII Village, BermaniUlu Raya District, RejangLebong Regency. Determination of respondents is done intentionally, namely as many as 26 respondents in the farm. The data analysis itself uses Spearman Rank Correlation analysis, Based on the results of the study, it is known that after conducting the Spearman Rank analysis, the following RESULTS were obtained. (1) Workers' perceptions of Pak Dasman's laying hens tend to be quite good (2) he attitude of workers towards Pak Dasman's laying hens farm tends to be quite positive (3) The factors that are significantly related to workers' perceptions of Pak Dasman's laying hens farm are education, expectations and interests, while age and experience have no significant relationship, (4) Perceptions related to the attitude of workers towards Pak Daman's laying hens farm obtained a tcount of 3.395 with a 95% confidence level or t0.05 = 1.1711, it can be concluded that H0 is rejected and Ha is accepted, which means that there is a real relationship between perceptions and attitudes of workers. against the laying hens farm owned by Mr. Dasman. Keywords: Perception, Attitude, Factors Related To Perception